Pharyngeal spasticity due to dantrolene. (12th April 2014) - Locatelli, F.; Pozzi, M.; Avantaggiato, P.; Lanfranchi, M.; Tufarulo, L.; Amorelli, V.; Rizzi, G.; Radice, S.; Galbiati, S.; Clementi, E.; Strazzer, S.
Summary What is known and objective Dantrolene can be combined with baclofen to better treat spasticity, but may cause muscular weakness and dysphagia. We instead describe a pharyngeal spasm due to dantrolene. Case summary A 12‐year‐old male received dantrolene 3 mg/kg/day in adjunct to baclofen 2 mg/kg/day, to improve spasticity. After 5 days of full‐dose dantrolene, his dysphagia worsened and he developed pharyngeal spasm. Dantrolene was suspected for an adverse reaction and removed. The patient subsequently improved. What is new and conclusion Causality analysis determined a probable relationship between dantrolene and pharyngeal spasm. This may be due to direct muscle contraction by dantrolene, an effect seen previously in vitro.